Application of tetrathiafulvalene derivative, lithium-sulfur battery electrolyte, application of lithium-sulfur battery electrolyte and lithium-sulfur battery

By adding tetrasulfide-fullwaene derivatives to the lithium sulfur battery electrolyte, the electron transfer capability of lithium polysulfide is enhanced and the fluorinated SEI film is constructed, which solves the problem of lithium polysulfide shuttle effect in lithium sulfur batteries, and significantly improves the battery's cycle stability and long cycle performance.

CN120127222APending Publication Date: 2025-06-10INNER MONGOLIA UNIV FOR THE NATITIES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510302586.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-14
Publication Date
2025-06-10

AI Technical Summary

Technical Problem

The "shuttle effect" of lithium polysulfide in lithium-sulfur batteries leads to the consumption of active substances and corrosion of metal lithium, affecting the cycle stability and industrialization of the battery.

Method used

Tetrathio-fullwaxene derivatives, such as formyl tetrathio-fullwaxene or hydroxylated tetrathio-fullwaxene, are introduced into the lithium sulfur battery electrolyte, and the electron transfer capability of lithium polysulfide is enhanced by van der Waals force, and a fluorinated SEI film is constructed on the surface of metal lithium to protect the lithium negative electrode.

Benefits of technology

It effectively improves the circulation stability of lithium sulfur batteries, reduces the shuttle effect of lithium polysulfide, protects the metal lithium negative electrode, and significantly improves the long-cycle performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120127222A_ABST
    Figure CN120127222A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium-sulfur batteries, and provides application of a tetrathiafulvalene derivative, a lithium-sulfur battery electrolyte, application of the lithium-sulfur battery electrolyte and a lithium-sulfur battery. The tetrathiafulvalene derivative is applied to the lithium-sulfur battery electrolyte, and the tetrathiafulvalene derivative is formyl tetrathiafulvalene (the structure shown in the formula I) or hydroxylated tetrathiafulvalene (the structure shown in the formula II). According to the invention, the tetrathiafulvalene derivative is added into the electrolyte of the lithium-sulfur battery, and the tetrathiafulvalene derivative can be used as a catalyst for promoting an oxidation-reduction reaction of lithium polysulfide in the lithium-sulfur battery, so that the electron transfer capability during conversion of the lithium polysulfide is improved, and the utilization rate of active sulfur is improved; the shuttle effect of polysulfide is effectively reduced, the integrity of the lithium negative electrode is guaranteed, and the cycling stability of the lithium-sulfur battery is improved. The tetrathiafulvalene derivative can also be used as a film-forming agent for inhibiting the growth of lithium dendrites, so that the integrity of a lithium negative electrode is guaranteed, and the cycling stability of a lithium-sulfur battery is improved. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-sulfur batteries, and particularly to the application of tetrathiafulvalene derivatives, lithium-sulfur battery electrolytes and their applications, and lithium-sulfur batteries. Background Art

[0002] The theoretical energy density of lithium-sulfur batteries is 3 to 5 times higher than that of lithium-ion batteries, so it has received extensive attention in the scientific research community and the industrial community. However, there are still many unsolved problems in lithium-sulfur batteries. Among them, the "shuttle effect" of polysulfide seriously consumes the active substances inside the battery and causes irreversible corrosion to metallic lithium, which is the "high threshold" for the industrialization process of lithium-sulfur batteries. Introducing a small amount of additives into the electrolyte of lithium-sulfur batteries can effectively improve the above problems.

[0003] In the related prior art, tetrathiafulvalene is added to the electrolyte of lithium-sulfur batteries. The lithium-sulfur battery composed of the above electrolyte has an increased discharge specific capacity, but has the problem of poor cycle stability. Summary of the Invention

[0004] In view of this, the purpose of the present invention is to provide the application of tetrathiafulvalene derivatives, lithium-sulfur battery electrolytes and their applications, and lithium-sulfur batteries. The present invention applies tetrathiafulvalene derivatives to the electrolyte of lithium-sulfur batteries, improving the cycle stability of lithium-sulfur batteries.

[0005] In order to achieve the above-mentioned invention purpose, the present invention provides the following technical solutions:

[0006] The present invention provides the application of tetrathiafulvalene derivatives in the electrolyte of lithium-sulfur batteries, and the tetrathiafulvalene derivatives are formyltetrathiafulvalene or hydroxylated tetrathiafulvalene;

[0007] The formyltetrathiafulvalene has the structure shown in Formula I:

[0008]

[0009] The hydroxylated tetrathiafulvalene has the structure shown in Formula II:

[0010]

[0011] The present invention provides a lithium-sulfur battery electrolyte, including tetrathiafulvalene derivatives, lithium bis(trifluoromethanesulfonyl)imide, lithium nitrate, 1,3-dioxolane and ethylene glycol dimethyl ether;

[0012] The tetrathiafulvalene derivatives are formyltetrathiafulvalene or hydroxylated tetrathiafulvalene.

[0013] Preferably, the concentration of the tetrathiafulvalene derivatives in the lithium-sulfur battery electrolyte is 0.01 to 0.1 mol / L.

[0014] Preferably, the concentration of lithium bis(trifluoromethanesulfonyl)imide in the lithium-sulfur battery electrolyte is 1 to 2 mol / L.

[0015] Preferably, the concentration of lithium nitrate in the lithium-sulfur battery electrolyte is 0.01 to 0.1 mol / L.

[0016] Preferably, the volume ratio of 1,3-dioxolane to ethylene glycol dimethyl ether is 1:1.

[0017] The present invention also provides a lithium-sulfur battery, comprising a positive electrode, a negative electrode, an electrolyte, and a separator, wherein the electrolyte is the lithium-sulfur battery electrolyte described in the above technical solution.

[0018] Preferably, the positive electrode includes sulfur, and the negative electrode is a lithium sheet.

[0019] Preferably, the areal loading of sulfur in the positive electrode is 2 to 5 mg / cm 2 .

[0020] Preferably, the ratio of the volume of the electrolyte to the mass of sulfur in the positive electrode is 7 to 20 μL:1 mg.

[0021] The present invention provides an application of tetrathiafulvalene derivatives in a lithium-sulfur battery electrolyte.

[0022] The present invention applies formyltetrathiafulvalene or hydroxylated tetrathiafulvalene to the lithium-sulfur battery electrolyte, and the lithium-sulfur battery composed of the above lithium-sulfur battery electrolyte has excellent long-cycle stability.

[0023] The present invention also provides a lithium-sulfur battery electrolyte.

[0024] The present invention applies tetrathiafulvalene derivatives (formyltetrathiafulvalene (TTF-CHO) or hydroxylated tetrathiafulvalene (TTF-CH 2When the tetrathiafulvalene derivative is added to the electrolyte of the lithium-sulfur battery, it interacts with lithium polysulfide through van der Waals forces, improving the electron transfer ability during the conversion of lithium polysulfide, enhancing the utilization rate of the active material sulfur, effectively reducing the shuttle effect of polysulfides, ensuring the integrity of the lithium negative electrode, and improving the cycle stability of the lithium-sulfur battery. At the same time, the tetrathiafulvalene derivative can reduce the energy level difference between the LUMO and HOMO of lithium polysulfide, accelerate the conversion rate of lithium polysulfide, and effectively promote the decomposition of lithium salts. Generally speaking, the tetrathiafulvalene derivative has the function of a catalyst that promotes the redox reaction of lithium polysulfide in the lithium-sulfur battery. In addition, the tetrathiafulvalene derivative will also construct a fluorinated SEI film on metallic lithium. The construction of the SEI film can inhibit lithium dendrites, ensure the integrity of the lithium negative electrode, protect metallic lithium from corrosion by lithium polysulfide, and accelerate the diffusion ability of lithium ions at the negative electrode interface, thereby improving the cycle stability of the lithium-sulfur battery.

[0025] The data of the examples show that the lithium-sulfur battery added with TTF-CHO can still maintain a high capacity of 439.1 mAh·g under a high current density of 1C after 500 cycles. -1 In the soft-pack battery, the lithium-sulfur battery containing TTF-CH 2 OH can stably cycle 30 times and maintain a specific capacity of 1009 mAh·g. -1 Description of the Drawings

[0026] Figure 1 Fig. is the first-cycle galvanostatic charge-discharge test curves of lithium-sulfur batteries with different TTF-CHO contents at a rate of 0.1C.

[0027] Figure 2 Fig. is the first-cycle cyclic voltammetry (CV) test curves of the control group (blank) and the experimental group (TTF-CHO) lithium-sulfur batteries.

[0028] Figure 3 Fig. is the first-cycle galvanostatic charge-discharge test curves of the control group (blank) and the experimental group (TTF-CHO) lithium-sulfur batteries at a rate of 0.1C.

[0029] Figure 4 Fig. is the GITT comparison chart of the control group (blank) and the experimental group (TTF-CHO) lithium-sulfur batteries.

[0030] Figure 5 Fig. is the comparison chart of the discharge capacities of the control group (blank) and the experimental group (TTF-CHO) lithium-sulfur batteries at different rates.

[0031] Figure 6SEM images of the surface (a - b) and cross - section (c - d) of lithium metal after 100 cycles of lithium - sulfur batteries for the control group (blank) and the experimental group (TTF - CHO);

[0032] Figure 7 XPS spectra of N and F elements on the surface of lithium metal after 100 cycles of lithium - sulfur batteries for the control group (a) and the experimental group (b);

[0033] Figure 8 Rate cycling curves of lithium - lithium symmetric batteries for the control group (blank) and the experimental group (TTF - CHO);

[0034] Figure 9 Long - cycle curves of lithium - lithium symmetric batteries for the control group (blank) and the experimental group (TTF - CHO);

[0035] Figure 10 Magnified cycling curves of lithium - lithium symmetric batteries for the control group (blank) and the experimental group (TTF - CHO) during 154 - 166 h of cycling;

[0036] Figure 11 Magnified cycling curves of lithium - lithium symmetric batteries for the control group (blank) and the experimental group (TTF - CHO) during 260 - 270 h of cycling;

[0037] Figure 12 Discharge capacity comparison curves of lithium - sulfur batteries for the control group (TTF) and the experimental group (TTF - CHO) at 1C;

[0038] Figure 13 For the first - cycle galvanostatic charge - discharge test curves of lithium - sulfur batteries with different TTF - CH 2 OH contents at a rate of 0.1C;

[0039] Figure 14 First - cycle cyclic voltammetry (CV) test curves of lithium - sulfur batteries for the control group (blank) and the experimental group (TTF - CH 2 OH);

[0040] Figure 15 First - cycle galvanostatic charge - discharge test curves of lithium - sulfur batteries for the control group (blank) and the experimental group (TTF - CH 2 OH) at a rate of 0.1C;

[0041] Figure 16 GITT comparison curves of lithium - sulfur batteries for the control group (blank) and the experimental group (TTF - CH 2 OH);

[0042] Figure 17 For the control group (blank) and the experimental group (TTF - CH 2Comparison diagram of discharge capacities of lithium-sulfur batteries with OH at different rates;

[0043] Figure 18 For the control group (blank) and the experimental group (TTF-CH 2 SEM images of the surface (a - b) and cross-section (c - d) of metallic lithium after 100 cycles of lithium-sulfur batteries with OH;

[0044] Figure 19 Discharge capacity diagram of lithium-sulfur battery at 0.1C;

[0045] Figure 20 For the experimental group (TTF-CH 2 Discharge capacity diagrams of lithium-sulfur batteries with OH and the control groups (TTF-CHO and blank) at 0.1C;

[0046] Figure 21 Appearance photo of a soft-pack lithium-sulfur battery;

[0047] Figure 22 Discharge capacity of a soft-pack lithium-sulfur battery at a rate of 0.05C;

[0048] Figure 23 For the control group (TTF) and the experimental group (TTF-CH 2 Comparison diagram of discharge capacities of lithium-sulfur batteries with OH at 1C. Detailed implementation mode

[0049] The present invention provides an application of tetrathiafulvalene derivatives in the electrolyte of lithium-sulfur batteries, and the tetrathiafulvalene derivatives are formyltetrathiafulvalene or hydroxylated tetrathiafulvalene;

[0050] The formyltetrathiafulvalene has the structure shown in Formula I:

[0051]

[0052] The hydroxylated tetrathiafulvalene has the structure shown in Formula II:

[0053]

[0054] In the present invention, the preparation method of the hydroxylated tetrathiafulvalene preferably includes the following steps: After mixing formyltetrathiafulvalene and methanol, add NaBH 4 Perform a hydroxylation reaction to obtain the hydroxylated tetrathiafulvalene. In the present invention, the mixing is preferably carried out under an ice-water bath and stirring conditions. In the present invention, the mass ratio of formyltetrathiafulvalene to NaBH 4 is preferably 1:4. In the present invention, the dosage ratio of formyltetrathiafulvalene to methanol is preferably 50mg:15mL. In the present invention, the NaBH4 It is preferably added in batches. The hydroxylation reaction is preferably carried out under an ice-water bath and stirring conditions, and the time of the hydroxylation reaction is preferably 8 to 14 h, specifically preferably 8 h, 10 h, 12 h or 14 h. After the hydroxylation reaction, the present invention preferably further includes: drying the obtained reaction liquid to obtain the hydroxylated tetrathiafulvalene; the present invention does not specifically limit the temperature and time of the drying, as long as the methanol can be completely removed.

[0055] The present invention adds a tetrathiafulvalene derivative to the lithium-sulfur battery electrolyte. In addition to the van der Waals force, the interaction relationship between the tetrathiafulvalene derivative and polysulfide lithium can reduce the LUMO energy level of polysulfide lithium, accelerate the conversion rate of polysulfide lithium, and effectively promote the decomposition of lithium salts; it can also construct a fluorinated SEI on metallic lithium, protect metallic lithium from corrosion by polysulfide lithium, and accelerate the diffusion ability of lithium ions at the negative electrode interface, thereby improving the cycle stability of the lithium-sulfur battery.

[0056] The present invention also provides a lithium-sulfur battery electrolyte, which includes a tetrathiafulvalene derivative, lithium bis(trifluoromethanesulfonyl)imide, lithium nitrate, 1,3-dioxolane and ethylene glycol dimethyl ether; the tetrathiafulvalene derivative is formyltetrathiafulvalene (TTF-CHO) or hydroxylated tetrathiafulvalene (TTF-CH 2 OH).

[0057] Unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.

[0058] The lithium-sulfur battery electrolyte provided by the present invention includes a tetrathiafulvalene derivative, and the tetrathiafulvalene derivative is formyltetrathiafulvalene or hydroxylated tetrathiafulvalene.

[0059] In the present invention, the formyltetrathiafulvalene has the structure shown in Formula I:

[0060]

[0061] In the present invention, the hydroxylated tetrathiafulvalene has the structure shown in Formula II:

[0062]

[0063] In the present invention, the concentration of the tetrathiafulvalene derivative in the lithium-sulfur battery electrolyte is preferably 0.01 to 0.1 mol / L, more preferably 0.025 to 0.075 mol / L, still more preferably 0.05 mol / L, and specifically preferably 0.01 mol / L, 0.02 mol / L, 0.025 mol / L, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.075 mol / L, 0.08 mol / L, 0.09 mol / L or 0.1 mol / L.

[0064] The lithium-sulfur battery electrolyte provided by the present invention includes lithium bis(trifluoromethanesulfonyl)imide (LiTFSI). In the present invention, the concentration of lithium bis(trifluoromethanesulfonyl)imide in the lithium-sulfur battery electrolyte is preferably 1 to 2 mol / L, and specifically preferably 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L or 2 mol / L.

[0065] The lithium-sulfur battery electrolyte provided by the present invention includes lithium nitrate. In the present invention, the concentration of lithium nitrate in the lithium-sulfur battery electrolyte is preferably 0.01 to 0.1 mol / L, and specifically preferably 0.01 mol / L, 0.02 mol / L, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L or 0.1 mol / L.

[0066] The lithium-sulfur battery electrolyte provided by the present invention includes 1,3-dioxolane and ethylene glycol dimethyl ether. In the present invention, the volume ratio of 1,3-dioxolane to ethylene glycol dimethyl ether is preferably 1:1.

[0067] The present invention does not specifically limit the preparation method of the lithium-sulfur battery electrolyte, and any mixture preparation method well-known to those skilled in the art can be used.

[0068] In the present invention, lithium bis(trifluoromethanesulfonyl)imide, lithium nitrate, 1,3-dioxolane and ethylene glycol dimethyl ether are preferably the formulation and components of a traditional lithium-sulfur battery electrolyte. In a specific embodiment of the present invention, the preparation method of the lithium-sulfur battery electrolyte preferably includes the following steps: adding the tetrathiafulvalene derivative to the traditional lithium-sulfur battery electrolyte.

[0069] The present invention also provides the application of the lithium-sulfur battery electrolyte described in the above technical solution in a lithium-sulfur battery.

[0070] The present invention also provides a lithium-sulfur battery, comprising a positive electrode, a negative electrode, an electrolyte, and a separator, wherein the electrolyte is the lithium-sulfur battery electrolyte described in the above technical solution.

[0071] The lithium-sulfur battery provided by the present invention comprises a positive electrode, and the positive electrode comprises elemental sulfur. Preferably, the positive electrode further comprises a carrier for loading the elemental sulfur. In the present invention, the carrier preferably comprises ordered mesoporous carbon CMK-3, ordered mesoporous carbon SP, or aluminum foil, and more preferably ordered mesoporous carbon CMK-3. In the present invention, the areal loading of elemental sulfur in the positive electrode is preferably 2-5 mg / cm 2 , specifically preferably 2 mg / cm 2 , 2.5 mg / cm 2 , 3 mg / cm 2 , 3.5 mg / cm 2 , 4 mg / cm 2 , 4.5 mg / cm 2 or 5 mg / cm 2 .

[0072] The lithium-sulfur battery provided by the present invention comprises a negative electrode, and the negative electrode is preferably a lithium sheet.

[0073] The lithium-sulfur battery provided by the present invention comprises an electrolyte, and the electrolyte is the lithium-sulfur battery electrolyte described in the above technical solution. In the present invention, the ratio of the volume of the electrolyte to the mass of elemental sulfur in the positive electrode is preferably 7-20 μL:1 mg, specifically preferably 7 μL:1 mg, 8 μL:1 mg, 9 μL:1 mg, 10 μL:1 mg, 11 μL:1 mg, 12 μL:1 mg, 13 μL:1 mg, 14 μL:1 mg, 15 μL:1 mg, 16 μL:1 mg, 17 μL:1 mg, 18 μL:1 mg, 19 μL:1 mg, or 20 μL:1 mg.

[0074] The lithium-sulfur battery provided by the present invention comprises a separator, and the separator is preferably a Celgard separator.

[0075] The lithium-sulfur battery provided by the present invention preferably further comprises an external circuit, and the present invention does not specifically limit the structure of the external circuit.

[0076] The lithium-sulfur battery electrolyte, its application, and the lithium-sulfur battery provided by the present invention will be described in detail below with reference to examples, but they should not be construed as limiting the protection scope of the present invention.

[0077] Raw materials used in the following examples: formyltetrathiafulvalene (Maclean's reagent, 99.9%), lithium sheet (Zhongneng Lithium Industry, 15.6 mm), separator (Celgard, 2400).

[0078] Example 1

[0079] Add formyltetrathiafulvalene to 10 mL of a commercial lithium-sulfur battery electrolyte (including LiTFSI, lithium nitrate, 1,3-dioxolane, and ethylene glycol dimethyl ether, where the concentration of LiTFSI is 1 mol / L, the concentration of lithium nitrate is 0.01 mol / L, and the volume ratio of 1,3-dioxolane to ethylene glycol dimethyl ether is 1:1) to obtain a lithium-sulfur battery electrolyte containing formyltetrathiafulvalene. In the lithium-sulfur battery electrolyte containing formyltetrathiafulvalene, the concentrations of formyltetrathiafulvalene are 0.025 mol / L, 0.05 mol / L, and 0.1 mol / L, respectively.

[0080] Take 60 μL of lithium-sulfur battery electrolytes with different concentrations of formyltetrathiafulvalene and add them to lithium-sulfur batteries (where the negative electrode is a lithium sheet, the positive electrode is sulfur, the areal loading of sulfur is 2 mg / cm -2 , the total loading of sulfur is 3 mg, and the separator is a Celgard separator), and perform electrochemical tests using a land test system and a BioLogic electrochemical workstation. The results are as Figure 1 shown. Figure 1 Figure 0.1C is the first-cycle galvanostatic charge-discharge test curve of lithium-sulfur batteries with different TTF-CHO contents. From Figure 1 it can be seen that when the concentration of formyltetrathiafulvalene is 0.05 mol / L, it has the highest discharge specific capacity. Therefore, for subsequent electrochemical tests, formyltetrathiafulvalene with a concentration of 0.05 mol / L is selected as the electrolyte additive.

[0081] Example 2

[0082] Take the lithium-sulfur battery electrolyte containing formyltetrathiafulvalene with a concentration of 0.05 mol / L as the experimental group and the commercial lithium-sulfur battery electrolyte as the control group.

[0083] Take 60 μL of the lithium-sulfur battery electrolyte containing formyltetrathiafulvalene and add it to a lithium-sulfur battery (where the negative electrode is a lithium sheet, the positive electrode is sulfur, the areal loading of sulfur is 2 mg / cm -2 , the total loading of sulfur is 3 mg, and the separator is a Celgard separator), and add 60 μL of the commercial lithium-sulfur battery electrolyte to the lithium-sulfur battery.

[0084] Perform electrochemical tests on the assembled lithium-sulfur batteries using a land test system and a BioLogic electrochemical workstation. The test results are shown in Figures 2 to 5 .

[0085] Figure 2 Figure is the first-cycle cyclic voltammetry (CV) test curve of the control group (blank) and experimental group (TTF-CHO) lithium-sulfur batteries. From Figure 2It can be seen that both types of batteries exhibit the typical redox characteristic peaks of lithium-sulfur batteries. The oxidation peak (2.35 V) of the experimental group's lithium-sulfur battery is lower than that of the control group's lithium-sulfur battery (2.41 V), and the reduction peak (1.98 V) of the experimental group's lithium-sulfur battery is higher than that of the control group's lithium-sulfur battery (1.95 V). At the same time, the experimental group's lithium-sulfur battery has a higher peak current. This result corresponds to the theoretical calculation result, indicating that TTF-CHO can improve the redox kinetics of polysulfide.

[0086] To further explore the ability of TTF-CHO to accelerate the conversion kinetics of sulfur, constant current charge-discharge tests were conducted on the lithium-sulfur batteries of the control group and the experimental group. The results are as Figure 3 shown. Figure 3 Figure shows the first-cycle constant current charge-discharge test curves of the lithium-sulfur batteries of the control group (blank) and the experimental group (TTF-CHO) at a rate of 0.1C. From Figure 3 it can be seen that the first-cycle specific capacity of the lithium-sulfur battery in the experimental group with TTF-CHO added is 1293.4 mAh·g -1 , which is higher than that of the lithium-sulfur battery in the control group without TTF-CHO added (959 mAh·g -1 ). Moreover, compared with the lithium-sulfur battery in the control group without TTF-CHO added, the lithium-sulfur battery in the experimental group with TTF-CHO added has a smaller polarization voltage. This test result corresponds to the previous CV test result.

[0087] After the first-cycle discharge of the lithium-sulfur battery, a galvanostatic intermittent titration technique (GITT) test was carried out. The results are as Figure 4 shown. Figure 4 Figure shows the GITT comparison chart of the lithium-sulfur batteries of the control group (blank) and the experimental group (TTF-CHO). From Figure 4 it can be seen that the lithium-sulfur battery in the experimental group with TTF-CHO added has a smaller polarization voltage.

[0088] To further evaluate the rate performance, the lithium-sulfur battery was tested at rates of 0.1C, 0.2C, 0.5C, 1C, 2C, and 0.1C. The results are as Figure 5 shown. Figure 5 Figure shows the comparison chart of the discharge capacities of the lithium-sulfur batteries of the control group (blank) and the experimental group (TTF-CHO) at different rates. From Figure 5 it can be seen that the capacities of the lithium-sulfur batteries in the experimental group containing TTF-CHO are 1156.1 mAh·g -1 , 896.9 mAh·g -1 , 776.4 mAh·g -1 , 696 mAh·g -1 , 642.3 mAh·g -1, 749.6 mAh·g -1 , which is higher than that of the control group lithium-sulfur battery without TTF-CHO, proving that TTF-CHO improves the rate performance of lithium-sulfur batteries to a certain extent.

[0089] Figures 2 to 5 Overall, TTF-CHO can reduce the E gap value of polysulfide, thereby improving the redox kinetics of polysulfide. Therefore, TTF-CHO has excellent cycle stability, fast kinetics and rate performance, and high capacity retention.

[0090] After disassembling the lithium-sulfur battery after 100 cycles at a 0.1C rate, the surface and cross-section of its lithium negative electrode were analyzed by SEM. The results are as Figure 6 shown Figure 6 are SEM images of the surface (a - b) and cross-section (c - d) of metallic lithium of the control group (blank) and experimental group (TTF-CHO) lithium-sulfur batteries after 100 cycles. It can be seen from Figure 6 that for the lithium-sulfur battery of the control group without TTF-CHO, the surface of the lithium negative electrode is severely corroded and shows a mossy shape, and the cross-section is uneven and there is also corrosion in the depth; for the lithium-sulfur battery of the experimental group containing TTF-CHO, the surface of the lithium is relatively smooth and flat, and a layer of SEI appears on the cross-section, and no corrosion phenomenon is found in the depth. It is proved that this layer of SEI effectively alleviates the side reaction between metallic lithium and polysulfide. Therefore, the lithium-sulfur battery of the experimental group with TTF-CHO shows good electrochemical stability. TTF-CHO can assist in constructing a dense SEI on the surface of metallic lithium, effectively protecting metallic lithium, which confirms the reason for the performance improvement of TTF-CHO during the cycling process of lithium-sulfur batteries.

[0091] After disassembling the lithium-sulfur battery after 100 cycles at a 0.1C rate, XPS test was carried out on the surface of the lithium negative electrode to analyze the components of SEI. The results are as shown in Figure 7. Figure 7 are XPS test N and F element spectra of the surface of metallic lithium of the control group (a) and experimental group (b) lithium-sulfur batteries after 100 cycles. As Figure 7 shown, the components of the SEI on the lithium negative electrode of the lithium-sulfur battery composed of adding and not adding TTF-CHO are the same but the peak intensities are different. In the F1s spectrum, there are two peaks at 688.2 eV and 684.1 eV. The peak at 684.1 eV belongs to the LiF bond, which is the main component of the SEI after adding TTF-CHO. Through the comparison of the peak intensities of the F1s spectrum, it shows that the SEI formed on the surface of metallic lithium after adding TTF-CHO contains more LiF. TTF-CHO can also effectively promote the conversion of LiTFSI to LiF to construct a fluorinated SEI, forming an SEI with high ionic conductivity and capable of protecting the metallic lithium negative electrode.

[0092] Testing at different current densities and constant current for long cycles is one of the most intuitive methods to evaluate the electrochemical deintercalation / insertion behavior of TTF-CHO with metallic lithium.

[0093] Lithium-lithium symmetric cells were assembled with the electrolyte containing formyltetrathiafulvalene lithium-sulfur battery and the commercial lithium-sulfur battery electrolyte respectively for electrochemical performance testing. The cycling performance of the lithium-lithium symmetric cells was detected in the range of current density from 0.5 to 2 mA·cm -2 . The results are as Figure 8 shown. Figure 8 Figure 9 is the rate cycling diagram of the lithium-lithium symmetric cells of the control group (blank) and the experimental group (TTF-CHO). As Figure 8 shown, the polarization voltage of the lithium-lithium symmetric cell of the control group without TTF-CHO is serious, while the lithium-lithium symmetric cell of the experimental group containing TTF-CHO shows a stable and smaller polarization voltage.

[0094] The lithium-lithium symmetric cells of the control group and the experimental group were tested for long cycles at a current density of 1 mA·cm -2 . The results are as Figure 9 shown. Figure 9 Figure 10 is the long cycle diagram of the lithium-lithium symmetric cells of the control group (blank) and the experimental group (TTF-CHO). It can be seen from Figure 9 Figure 10 that the lithium-lithium symmetric cell of the experimental group containing TTF-CHO can cycle stably for 2000 h and be in a stable working state at 200 h, while the lithium-lithium symmetric cell of the control group without TTF-CHO has serious voltage polarization and is in a short-circuit state after 400 h. This phenomenon can be attributed to the continuous growth of lithium dendrites, which causes the battery to transition from an early relatively stable state to a final break, and at the same time, it also reflects that it is difficult to construct a stable SEI for the battery without TTF-CHO.

[0095] Figure 10 Figure 11 is the enlarged cycle diagram of the lithium-lithium symmetric cells of the control group (blank) and the experimental group (TTF-CHO) during 154 - 166 h of cycling. It can be observed from Figure 10 Figure 11 that the initial polarization voltage of the lithium-lithium symmetric cell of the experimental group with TTF-CHO is still smaller than that of the lithium-lithium symmetric cell of the control group without TTF-CHO.

[0096] Figure 11 Figure 12 is the enlarged cycle diagram of the lithium-lithium symmetric cells of the control group (blank) and the experimental group (TTF-CHO) during 260 - 270 h of cycling. It can be seen from Figure 11 Figure 12 that the polarization voltage of the lithium-lithium symmetric cell of the experimental group containing TTF-CHO has been stabilized at 0.016 V. This means that TTF-CHO can effectively stabilize the metallic lithium interface.

[0097] Example 3

[0098] The electrolyte of the lithium-sulfur battery containing formyltetrathiafulvalene with a concentration of 0.05 mol / L was used as the experimental group.

[0099] Tetrathiafulvalene (TTF) with a concentration of 0.05 mol / L was added to the commercial lithium-sulfur battery electrolyte to form a lithium-sulfur battery electrolyte containing tetrathiafulvalene, which was used as the control group.

[0100] Take 60 μL of the lithium-sulfur battery electrolyte containing formyltetrathiafulvalene and add it to a lithium-sulfur battery (wherein, the negative electrode is a lithium sheet, the positive electrode is sulfur, the areal loading of sulfur is 2 mg / cm -2 , the total loading of sulfur is 3 mg, and the separator is a Celgard separator), and 60 μL of the lithium-sulfur battery electrolyte containing tetrathiafulvalene was added to the lithium-sulfur battery.

[0101] The assembled lithium-sulfur battery was subjected to electrochemical tests using a land test system and a BioLogic electrochemical workstation.

[0102] Figure 12 Figure showing the comparison of discharge capacities of the lithium-sulfur batteries of the control group (TTF) and the experimental group (TTF-CHO) at 1C. From Figure 12 It can be seen that: at high currents, the battery containing TTF-CHO has a higher discharge specific capacity, showing an extremely low capacity decay rate, only decaying by 0.9% per cycle, indicating that TTF-CHO has a good catalytic conversion effect on polysulfides.

[0103] Example 4

[0104] The preparation method of hydroxylated tetrathiafulvalene is as follows:

[0105] Take 50 mg of formyltetrathiafulvalene (TTF-CHO) and dissolve it in 15 mL of methanol, and stir it thoroughly with a magnetic stirrer in an ice-water bath; then add 200 mg of NaBH in 3 batches 4 , and carry out a hydroxylation reaction for 12 h under the conditions of an ice-water bath and stirring, and then perform a drying treatment to obtain hydroxylated tetrathiafulvalene.

[0106] The hydroxylated tetrathiafulvalene was added to 10 mL of the commercial lithium-sulfur battery electrolyte (including LiTFSI, lithium nitrate, 1,3-dioxolane, and ethylene glycol dimethyl ether; wherein, the concentration of LiTFSI is 1 mol / L, the concentration of lithium nitrate is 0.01 mol / L, and the volume ratio of 1,3-dioxolane to ethylene glycol dimethyl ether is 1:1) to obtain an electrolyte containing hydroxylated tetrathiafulvalene, wherein the concentration of hydroxylated tetrathiafulvalene is 0.025 mol / L, 0.05 mol / L, or 1 mol / L, respectively.

[0107] 60 μL of electrolytes containing hydroxylated tetrathiafulvalene at different concentrations were respectively added to lithium-sulfur batteries (wherein, the negative electrode is a lithium sheet, the positive electrode includes a carrier (aluminum foil) and sulfur, and the areal loading of sulfur is 2 mg / cm 2 , and the separator is a Celgard separator). The ratio of the volume of the electrolyte to the mass of sulfur in the positive electrode is 20 μL / mg; electrochemical tests were carried out using a land test system and a BioLogic electrochemical workstation, and the results are as Figure 13 shown. Figure 13 Figure 2 shows the first-cycle galvanostatic charge-discharge test curves of lithium-sulfur batteries with different TTF-CH Figure 13 OH contents at a 0.1C rate. It can be seen from

[0108] Example 5

[0109] : The lithium-sulfur battery electrolyte containing hydroxylated tetrathiafulvalene at a concentration of 0.05 mol / L was used as the experimental group, and the commercial lithium-sulfur battery electrolyte was used as the control group.

[0110] 60 μL of the lithium-sulfur battery electrolyte containing hydroxylated tetrathiafulvalene was added to a lithium-sulfur battery (wherein, the negative electrode is a lithium sheet, the positive electrode is sulfur, the areal loading of sulfur is 2 mg / cm -2 , and the total loading of sulfur is 3 mg, and the separator is a Celgard separator), and 60 μL of the commercial lithium-sulfur battery electrolyte was added to the lithium-sulfur battery.

[0111] The assembled lithium-sulfur batteries were subjected to electrochemical tests using a land test system and a BioLogic electrochemical workstation, and the test results are shown in Figures 14 to 17 .

[0112] Figure 14 Figure 2 shows the first-cycle cyclic voltammetry (CV) test curves of the lithium-sulfur batteries of the control group (blank) and the experimental group (TTF-CH Figure 14 OH). It can be seen from 2 that both types of batteries exhibit the classic redox characteristic peaks of lithium-sulfur batteries. The oxidation peak (2.33 V) of the experimental group lithium-sulfur battery with TTF-CH 2 OH added is lower than that of the control group lithium-sulfur battery without TTF-CH 2 OH (2.41 V), and the reduction peak (2.01 V) of the experimental group lithium-sulfur battery with TTF-CH 2Reduction peak (1.95 V) of the control group lithium-sulfur battery with OH; while containing TTF-CH 2 The experimental group lithium-sulfur battery with OH has better peak current, which is much higher than that of the control group lithium-sulfur battery without adding TTF-CH 2 OH. At a scan rate of 0.1 mV / s, the peak current can reach ±8 mA.

[0113] To further explore the electrochemical performance of the lithium-sulfur battery, constant current charge and discharge tests were carried out on the control group and experimental group lithium-sulfur batteries, and the results are as Figure 15 shown. Figure 15 For the first cycle constant current charge and discharge test curves of the control group (blank) and experimental group (TTF-CH 2 OH) lithium-sulfur batteries at a 0.1C rate, from Figure 15 it can be seen that: the specific capacity of the experimental group lithium-sulfur battery with added TTF-CH 2 OH is 1360.4 mAh·g -1 , higher than that of the control group lithium-sulfur battery without adding TTF-CH 2 OH (959 mAh·g -1 ). And compared with the control group lithium-sulfur battery without adding TTF-CH 2 OH, the experimental group lithium-sulfur battery with added TTF-CH 2 OH has a smaller polarization voltage, and this test result corresponds to the CV test result.

[0114] Tested by constant current intermittent titration, the results are as Figure 16 shown. Figure 16 For the GITT comparison diagram of the control group (blank) and experimental group (TTF-CH 2 OH) lithium-sulfur batteries, from Figure 16 it can be seen that: the experimental group lithium-sulfur battery with added TTF-CH 2 OH has a smaller polarization voltage and more discharge capacity. This indicates that TTF-CH 2 OH can catalyze the conversion reaction of polysulfide lithium and improve the utilization rate of the active substance sulfur.

[0115] To further evaluate the rate performance, tests were carried out at 0.1C, 0.2C, 0.5C, 1C, 2C and 0.1C rates, and the results are as Figure 17 shown. Figure 17 For the discharge capacity comparison diagram of the control group (blank) and experimental group (TTF-CH 2 OH) lithium-sulfur batteries at different rates, from Figure 17 it can be seen that: the one containing TTF-CH 2The discharge capacities of the experimental group of lithium-sulfur batteries with TTF-CHOH were 1438.6 mAh·g -1 , 1116 mAh·g -1 , 966.1 mAh·g -1 , 866 mAh·g -1 , 799.3 mAh·g -1 , 923.9 mAh·g -1 , and the discharge capacities at each stage were higher than those of the control group of lithium-sulfur batteries without TTF-CH 2 OH. The experimental group of lithium-sulfur batteries with TTF-CH 2 OH showed better capacity retention ability.

[0116] After disassembling the lithium-sulfur battery cycled 100 times at a rate of 0.1C, the surface and cross-section of the lithium negative electrode were analyzed by SEM. The results are as Figure 18 shown. Figure 18 Figure shows the SEM images of the surface (a - b) and cross-section (c - d) of metallic lithium after 100 cycles for the control group (blank) and the experimental group (TTF-CH 2 OH) of lithium-sulfur batteries. It can be seen from Figure 18 that TTF-CH 2 OH can assist in constructing a dense SEI on the surface of metallic lithium, confirming the reason for the performance improvement of TTF-CH 2 OH during the cycling process of lithium-sulfur batteries. According to the test results shown in Figure 18 , it was found that for the control group of lithium-sulfur batteries without TTF-CH 2 OH, serious corrosion occurred on the surface of the lithium negative electrode, with the surface being uneven and signs of corrosion also existing deep inside. For the lithium-sulfur batteries with TTF-CH 2 OH, after cycling, the surface of the lithium negative electrode was relatively smooth and flat, and a dense SEI was formed on the surface, effectively protecting the lithium negative electrode, and no corrosion was found deep inside. This also verifies that the batteries with TTF-CH 2 OH can have a longer cycle life under harsh conditions.

[0117] Testing under harsh conditions of high areal loading and low liquid-to-sulfur ratio can directly reflect the sulfur conversion kinetic ability.

[0118] Example 6

[0119] Using an electrolyte containing hydroxylated tetrathiafulvalene with a concentration of 0.05 mol / L as the electrolyte, a lithium sheet as the negative electrode, and the positive electrode including a carrier and sulfur. The areal loading of sulfur is 3.4 mg / cm 2, in the case where the separator is a Celgard separator, the ratio (E / S) of the volume of the electrolyte to the mass of sulfur in the positive electrode is 8 μL / mg; electrochemical tests are carried out using a land test system and a BioLogic electrochemical workstation, and the results are as Figure 19 shown, Figure 19 the discharge capacity diagram of the lithium-sulfur battery at 0.1C. As Figure 19 shown, when the sulfur surface loading is 3.4 mg / cm 2 , and the liquid-sulfur ratio is 8 μL / mg, it can stably cycle 100 times.

[0120] Example 7

[0121] Using a hydroxyl-functionalized tetrathiafulvalene (TTF-CH 2 OH) electrolyte with a concentration of 0.05 mol / L, a formyltetrathiafulvalene (TTF-CHO) electrolyte with a concentration of 0.05 mol / L, or a commercial lithium-sulfur battery electrolyte as the electrolyte, a lithium foil as the negative electrode, and the positive electrode including a carrier and sulfur, the sulfur surface loading is 4.9 mg / cm 2 , in the case where the separator is a Celgard separator, the ratio (E / S) of the volume of the electrolyte to the mass of sulfur in the positive electrode is 8 μL / mg; electrochemical tests are carried out using a land test system and a BioLogic electrochemical workstation, and the results are as Figure 20 shown, Figure 20 the discharge capacity diagrams of the experimental group (TTF-CH 2 OH) and the control groups (TTF-CHO and blank) of lithium-sulfur batteries at 0.1C. As Figure 20 shown, when the sulfur loading is 4.9 mg / cm 2 , and the liquid-sulfur ratio is 8 μL / mg, the initial specific capacity of the experimental group of lithium-sulfur batteries containing TTF-CH 2 OH is 1210.4 mAh·g -1 , and there is still a reversible capacity of 665 mAh·g -1 after 67 cycles. The control group of lithium-sulfur batteries added with TTF-CHO showed a short-circuit situation when cycling less than 50 times. The control group of lithium-sulfur batteries without adding TTF-CH 2 OH and TTF-CHO had an initial specific capacity of 1098.2 mAh·g -1 , and a short-circuit overcharge situation occurred after 26 cycles, which is related to the shuttle effect and severe corrosion of metallic lithium. Introducing an electron-donating group (-CH 2(OH) has a stronger van der Waals force on LiPSs than when an electron-withdrawing group (-CHO) is introduced into the TTF molecule. Introducing an electron-donating group increases the electron cloud density of the TTF molecule in a specific region, thus promoting the formation of instantaneous dipoles. At the same time, the increase in such dipoles enhances the van der Waals force generated by the instantaneous dipoles, so it can further catalyze the conversion of lithium polysulfide.

[0122] Example 8

[0123] To further clarify the potential application of TTF-CH 2 OH, it was assembled into a pouch-type lithium-sulfur battery. Among them, the sulfur surface loading in the positive electrode was 8 mg / cm 2 , the total loading was 228 mg, and the ratio E / S of the volume of the electrolyte to the mass of sulfur in the positive electrode was as low as 5 μL / mg. The appearance photo of the obtained pouch-type lithium-sulfur battery is as Figure 21 shown.

[0124] The pouch-type lithium-sulfur battery was measured, and the results are as Figure 22 shown, Figure 22 which is the discharge capacity of the pouch-type lithium-sulfur battery at a rate of 0.05C. It can be seen from Figure 22 that the pouch-type lithium-sulfur battery shows an initial capacity of 282 mAh, corresponding to a specific discharge capacity of 1239 mAh·g -1 . Further shows that TTF-CH 2 OH has excellent cycle stability in the pouch-type lithium-sulfur battery, maintaining a discharge capacity of 225 mAh after 30 cycles, equivalent to a discharge capacity of 986 mAh·g -1 . These findings confirm the potential application of TTF-CH 2 OH in large-scale energy storage systems and indicate that the demand for electrolyte usage can be reduced.

[0125] Example 9

[0126] The lithium-sulfur battery electrolyte containing hydroxylated tetrathiafulvalene with a concentration of 0.05 mol / L was used as the experimental group.

[0127] Tetrathiafulvalene (TTF) with a concentration of 0.05 mol / L was added to the commercial lithium-sulfur battery electrolyte to form a lithium-sulfur battery electrolyte containing tetrathiafulvalene as the control group.

[0128] 60 μL of the lithium-sulfur battery electrolyte containing hydroxylated tetrathiafulvalene was added to a lithium-sulfur battery (the lithium sheet was used as the negative electrode, the positive electrode included a carrier and sulfur, the surface loading of sulfur was 2 mg / cm 2 , the total loading was 3 mg, and the separator was a Celgard separator), and 60 μL of the lithium-sulfur battery electrolyte containing tetrathiafulvalene was added to the lithium-sulfur battery.

[0129] The assembled lithium-sulfur battery was electrochemically tested using a land test system and a BioLogic electrochemical workstation.

[0130] Figure 23 Figure showing the comparison of discharge capacities of the control group (TTF) and the experimental group (TTF-CH 2 OH) lithium-sulfur batteries at 1C. It can be seen from Figure 23 that the battery containing TTF-CH 2 OH has an initial specific capacity of 1143.7 mAh g -1 , and still has a high reversible capacity of 547.4 mAh g -1 after cycling, with an average decay of 0.10% per cycle. However, the reversible capacity of the battery with added TTF decreases significantly with the number of cycles, and only 269.5 mAh g -1 of reversible capacity remains after 500 cycles. This indicates that the battery with added TTF-CH 2 OH benefits from the electron-donating group effect of the -OH group, which increases the electron cloud density within the molecule, further activates the additive, enhances the sulfur conversion rate of polysulfide lithium, and thus has faster conversion kinetics and a longer cycle life.

[0131] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements and refinements can be made, and these improvements and refinements should also be regarded as the protection scope of the present invention.

Claims

1. Application of tetrathiafulvalene derivatives in lithium-sulfur battery electrolyte, characterized in that: The tetrathiafulvalene derivative is formyltetrathiafulvalene or hydroxylated tetrathiafulvalene; The formyltetrathiafulvalene has a structure shown in Formula I: The hydroxylated tetrathiafulvalene has a structure shown in Formula II:

2. A lithium-sulfur battery electrolyte, characterized in that: including tetrathiafulvalene derivatives, lithium bis(trifluoromethanesulfonyl imide), lithium nitrate, 1,3-dioxolane, and ethylene glycol dimethyl ether; The tetrathiafulvalene derivative is formyltetrathiafulvalene or hydroxylated tetrathiafulvalene.

3. The lithium-sulfur battery electrolyte according to claim 2, characterized in that: The concentration of the tetrathiafulvalene derivative in the lithium-sulfur battery electrolyte is 0.01-0.1 mol / L.

4. The lithium-sulfur battery electrolyte according to claim 2, characterized in that: The concentration of lithium bis(trifluoromethanesulfonyl)imide in the lithium-sulfur battery electrolyte is 1-2 mol / L.

5. The lithium-sulfur battery electrolyte according to claim 2, characterized in that: The concentration of lithium nitrate in the lithium-sulfur battery electrolyte is 0.01-0.1 mol / L.

6. The lithium-sulfur battery electrolyte according to claim 2, characterized in that: The volume ratio of the 1,3-dioxolane to ethylene glycol dimethyl ether is 1:

1.

7. A lithium-sulfur battery comprising a positive electrode, a negative electrode, an electrolyte and a separator, characterized in that: The electrolyte is the lithium-sulfur battery electrolyte according to any one of claims 2 to 6.

8. The lithium-sulfur battery according to claim 7, characterized in that: The positive electrode includes sulfur, and the negative electrode is a lithium sheet.

9. The lithium-sulfur battery according to claim 8, characterized in that: The surface loading of sulfur in the positive electrode is 2 to 5 mg / cm 2 .

10. The lithium-sulfur battery according to claim 8, characterized in that: The ratio of the volume of the electrolyte to the mass of the sulfur element in the positive electrode is 7-20 μL:1 mg.